Cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite material, preparation method and application thereof, and cleaning method

By optimizing the combination of acidic agents, corrosion inhibitors and surfactants, a titanium-aluminum composite radial cleaning agent was developed, which solved the problem of insufficient cleaning power and corrosion of radial ash, achieved low temperature and efficient cleaning effect, and improved the Product quality and energy efficiency.

CN117758275BActive Publication Date: 2024-12-13SHENZHEN MEIRONGDA TECH CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202311737464.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-12-18
Publication Date
2024-12-13
Estimated Expiration
2043-12-18

AI Technical Summary

Technical Problem

The existing cleaning agents do not have enough cleaning power for titanium-aluminum composite materials, which is prone to corrosion of the surface of aluminum alloy, and requires a higher usage temperature, affecting product quality and energy efficiency.

Method used

Develop a cleaning agent for removing radium ash after titanium-aluminum composite material, containing acidic agents, corrosion inhibitors, solvents and water. By optimizing the proportion of components and adding surfactants and builders, a stable complex is formed. and protective film to improve cleaning effect.

Benefits of technology

It realizes effective removal of radium ash, protects the surface of aluminum alloy, reduces cleaning temperature, improves production efficiency and energy utilization, and ensures product cleanliness and brightness.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a cleaning agent for removing laser-carved dust after laser carving of a titanium-aluminum composite material. The cleaning agent comprises: an acidic agent, a corrosion inhibitor, a solvent and water; the acidic agent is selected from one or more of hydroxyethylidene diphosphonic acid, aminotris(methylene phosphonic acid), ethylenediaminetetra(methylene phosphonic acid) and diethylenetriaminepenta(methylene phosphonic acid); the corrosion inhibitor is selected from one or more of sodium benzotriazole, sodium mercaptobenzothiazole, methylbenzotriazole and imidazoline corrosion inhibitor; the solvent is selected from one or more of ethanol, glycerol, isopropanol, isohexanediol, diethylene glycol, propylene glycol methyl ether and dipropylene glycol butyl ether; the cleaning agent for removing laser-carved dust after laser carving of a titanium-aluminum composite material is scientifically screened and formulated, can completely clean and remove the laser-carved dust around titanium alloy, aluminum alloy and plastic jack after laser carving of the titanium-aluminum composite material, and has no adverse effect on the aluminum alloy; and has excellent cleaning effect on the laser-carved dust when used in ultrasonic wave at a cleaning temperature of 55°C.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of composite material cleaning, and in particular to a cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials, a preparation method and application thereof, and a method for cleaning using the cleaning agent. Background Art

[0002] Titanium-aluminum composite materials can be widely used in medical equipment, automobiles, energy, marine engineering, aerospace, military and other fields. Titanium-aluminum composite materials often need laser engraving machines to engrave the materials, so as to engrave the desired patterns or texts. After engraving, due to the strong temperature, laser engraving ash caused by high-temperature oxidation of aluminum alloy will be produced in the laser engraving area and near the laser engraving area. The composition of laser engraving ash is relatively complex, which is a mixture of titanium alloy oxides and aluminum alloy oxides. Since aluminum alloys are easily corroded by acids and alkalis during the cleaning process, when cleaning the laser engraving ash after laser engraving of titanium-aluminum composite materials, try not to use strong acids, strong alkalis, strong oxidants and other raw materials that may corrode aluminum alloys. This makes it more difficult to clean the laser engraving ash on titanium-aluminum composite materials.

[0003] Take the cleaning of mobile phone shells after laser engraving as an example. Currently, mobile phone shells are mostly made of titanium-aluminum composite materials. The front of the mobile phone shell is titanium alloy and the back is aluminum alloy. Such mobile phones have both the wear resistance and corrosion resistance of titanium alloy and the good electrical conductivity of aluminum alloy. After laser engraving, the laser engraving ash is distributed on the titanium alloy, aluminum alloy, and around the plastic jack, affecting the appearance of the product.

[0004] After high-temperature laser engraving, laser ash is distributed around titanium alloy, aluminum alloy and plastic sockets. It has complex composition, close bonding with titanium alloy, aluminum alloy and plastic, and strong adhesion. Currently, most commonly used cleaning agents are improved on the basis of the original aluminum alloy degreasing and waxing, or aluminum alloy deashing cleaning agents. When cleaning titanium aluminum composite laser ash, the following problems generally exist: 1. Insufficient cleaning power. Since the commonly used cleaning agents are not specially developed for titanium aluminum composite laser ash, the cleaning effect is generally poor, and the laser ash around titanium alloy, aluminum alloy and plastic sockets cannot be completely removed. 2. In order to enhance the cleaning power of titanium aluminum composite laser ash, the commonly used cleaning agents generally increase the acidity and alkalinity of the cleaning agent to improve the cleaning performance. Increasing the acidity and alkalinity of the cleaning agent will increase the corrosion to the aluminum alloy surface, which will have an adverse effect on the aluminum alloy surface and affect the quality of the product. 3. Since commonly used cleaning agents are not very effective in cleaning laser-engraved ash, a higher operating temperature is required, generally between 70°C and 75°C. Higher operating temperatures will in turn accelerate the corrosion of aluminum alloys and affect the brightness and performance of the aluminum alloy surface.

[0005] Therefore, it is particularly important to develop a cleaning agent that can solve the above problems and can effectively clean the laser engraving ash after laser engraving of titanium-aluminum composite materials, which has a good market prospect. Summary of the invention

[0006] The invention aims to solve the technical problem that the cleaning agent in the prior art has insufficient cleaning power for laser engraving ash and is corrosive to the surface of aluminum alloy.

[0007] The first aspect of the present invention provides a cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials, the cleaning agent comprising: an acidic agent, a corrosion inhibitor, a solvent and water; the acidic agent is selected from one or more of hydroxyethylidene diphosphonic acid, aminotri (methylene phosphonic acid), ethylenediaminetetra (methylene phosphonic acid), and diethylenetriaminepenta (methylene phosphonic acid); the corrosion inhibitor is selected from one or more of sodium benzotriazole, sodium mercaptobenzothiazole, methylbenzotriazole, and imidazoline corrosion inhibitor; the solvent is selected from one or more of ethanol, glycerol, isopropanol, isohexanediol, diethylene glycol, propylene glycol methyl ether, and dipropylene glycol butyl ether; in the cleaning agent, the weight proportions of each component are: 10 to 20 parts by weight of the acidic agent, 3 to 10 parts by weight of the corrosion inhibitor, 5 to 15 parts by weight of the solvent, and 40 to 60 parts by weight of water.

[0008] In the cleaning agent for removing laser engraving ash after laser engraving of the titanium-aluminum composite material of the present invention, preferably, the water is deionized pure water; the acidic agent is selected from at least two of hydroxyethylidene diphosphonic acid, aminotri (methylene phosphonic acid), ethylenediaminetetra (methylene phosphonic acid), and diethylenetriaminepenta (methylene phosphonic acid); the corrosion inhibitor is selected from at least two of sodium benzotriazole, sodium mercaptobenzothiazole, methylbenzotriazole, and imidazoline corrosion inhibitor; the solvent is selected from at least two of ethanol, glycerol, isopropanol, isohexanediol, diethylene glycol, propylene glycol methyl ether, and dipropylene glycol butyl ether; in the cleaning agent, the weight proportions of each component are: 40 to 45 parts by weight of pure water, 12 to 18 parts by weight of the acidic agent, 4 to 5 parts by weight of the corrosion inhibitor, and 8 to 12 parts by weight of the solvent.

[0009] In the cleaning agent for removing laser engraving ash after laser engraving of the titanium-aluminum composite material of the present invention, preferably, the cleaning agent also includes a surfactant and a builder; the surfactant is selected from one or more of alkyl glycosides, alkylphenol polyoxyethylene ethers, octylphenol polyoxyethylene ethers, sodium alkylbenzene sulfonates, isomeric tetradecanol polyoxyethylene ethers, and lauryl alcohol polyoxyethylene ethers; the builder is selected from one or more of sodium tripolyphosphate, sodium dihydrogen phosphate, potassium sodium tartrate, sodium carbonate, triethanolamine, and sodium sulfate; in the cleaning agent, the builder is 10 to 20 parts by weight, and the surfactant is 15 to 25 parts by weight.

[0010] In the cleaning agent for removing laser-engraved dust after laser engraving of the titanium-aluminum composite material of the present invention, preferably, the surfactant is selected from at least two of alkyl glucosides, alkylphenol polyoxyethylene ethers, octylphenol polyoxyethylene ethers, sodium alkylbenzene sulfonates, isomeric tetradecanol polyoxyethylene ethers, and lauryl alcohol polyoxyethylene ethers; the builder is selected from at least two of sodium tripolyphosphate, sodium dihydrogen phosphate, potassium sodium tartrate, sodium carbonate, triethanolamine, and sodium sulfate; in the cleaning agent, the builder is 12 to 18 parts by weight, and the surfactant is 18 to 25 parts by weight.

[0011] A second aspect of the present invention provides a method for preparing a cleaning agent for removing laser engraving dust after laser engraving of a titanium-aluminum composite material, comprising the following steps:

[0012] Steps for preparing pure water: weigh pure water and keep the temperature at 30-40℃;

[0013] The step of preparing a mixture containing an acidic agent is as follows: adding an acidic agent to pure water, stirring and dissolving the mixture completely, and obtaining a mixture containing an acidic agent; the acidic agent is selected from one or more of hydroxyethylidene diphosphonic acid, aminotrimethylphosphonic acid, ethylenediaminetetramethylphosphonic acid, and diethylenetriaminepentamethylphosphonic acid;

[0014] The step of preparing a mixture containing a corrosion inhibitor is as follows: adding the corrosion inhibitor to the mixture containing an acidic agent, stirring and dissolving the mixture completely, and obtaining a mixture containing an acidic agent and a corrosion inhibitor; the corrosion inhibitor is selected from one or more of sodium benzotriazole, sodium mercaptobenzothiazole, toluene triazole, and imidazoline corrosion inhibitor;

[0015] The step of preparing a mixture containing a solvent is as follows: adding a solvent to a mixture containing an acidic agent and a corrosion inhibitor, stirring and dissolving the solvent completely, and obtaining a cleaning agent for removing laser engraving ash after laser engraving of a titanium-aluminum composite material; the solvent is selected from one or more of ethanol, glycerol, isopropanol, isohexanediol, diethylene glycol, propylene glycol methyl ether, and dipropylene glycol butyl ether.

[0016] In the method for preparing a cleaning agent for removing laser engraving ash after laser engraving of a titanium-aluminum composite material of the present invention, preferably, between the step of preparing a mixture containing a corrosion inhibitor and the step of preparing a mixture containing a solvent, the following steps are further included:

[0017] The step of preparing a mixture containing a builder is as follows: adding the builder to a mixture containing an acidic agent and a corrosion inhibitor, stirring and dissolving the mixture completely, and obtaining a mixture containing an acidic agent, a corrosion inhibitor and a builder; the builder is selected from one or more of sodium tripolyphosphate, sodium dihydrogen phosphate, potassium sodium tartrate, sodium carbonate, triethanolamine, and sodium sulfate;

[0018] The steps of preparing a mixture containing a surfactant are as follows: adding a surfactant to a mixture containing an acidic agent, a corrosion inhibitor and a builder, stirring and dissolving the mixture completely, and obtaining a mixture containing an acidic agent, a corrosion inhibitor, a surfactant and a builder; then adding the solvent to the mixture, stirring and dissolving the mixture completely, and obtaining a cleaning agent for removing laser-engraved ash after laser engraving of a titanium-aluminum composite material; the surfactant is selected from a combination of one or more of alkyl glucoside, alkylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether, sodium alkylbenzene sulfonate, isomeric tetradecanol polyoxyethylene ether, and lauryl alcohol polyoxyethylene ether.

[0019] A third aspect of the present invention provides a method for cleaning a workpiece by removing laser engraving ash cleaning agent after laser engraving of a titanium-aluminum composite material, comprising the following steps:

[0020] Add an appropriate amount of pure water to the first ultrasonic cleaning tank, accurately weigh the cleaning agent for removing the laser carving ash after laser carving of the titanium-aluminum composite material, add it to the first ultrasonic cleaning tank, and prepare it into the first cleaning agent;

[0021] In a first ultrasonic cleaning tank, the workpiece to be cleaned is first cleaned with a first cleaning agent to obtain a first cleaned workpiece; wherein the workpiece to be cleaned is a titanium-aluminum composite material workpiece after laser engraving;

[0022] Add an appropriate amount of pure water to the second ultrasonic cleaning tank, accurately weigh the cleaning agent after laser engraving of the titanium-aluminum composite material to remove the laser engraving ash, add it to the second ultrasonic cleaning tank, and prepare it into the second cleaning agent;

[0023] Performing a second cleaning on the first cleaning workpiece in a second ultrasonic cleaning tank using a second cleaning agent to obtain a second cleaning workpiece;

[0024] The second cleaned workpiece is subjected to a triple water washing treatment, and after water washing, is dried at a temperature of 75 to 80° C. for 20 to 30 minutes to obtain a target workpiece.

[0025] In the method for cleaning workpieces by using a cleaning agent to remove laser ash after laser engraving of the titanium-aluminum composite material, preferably, the concentration of the cleaning agent for removing laser ash after laser engraving of the titanium-aluminum composite material in the first cleaning agent is 8% to 10%; the ultrasonic frequency and current of the first cleaning are 40 to 50 khz, 0.8 to 1.2 A, the temperature of the first cleaning is 50 to 55°C, and the cleaning time is 5 to 10 min; the concentration of the cleaning agent for removing laser ash after laser engraving of the titanium-aluminum composite material in the second cleaning agent is 8% to 10%; the ultrasonic frequency of the second cleaning is 40 to 50 khz, 0.8 to 1.2 A, the temperature of the second cleaning is 50 to 55°C, and the cleaning time is 5 to 10 min.

[0026] The fourth aspect of the present invention is to provide an application of a cleaning agent for removing laser engraving dust, the application including: application of preparing reagents or products for removing laser engraving dust; application of material cleaning; or application of using in conjunction with a laser engraving machine for workpiece production.

[0027] In the application of the cleaning agent for removing laser engraving dust, preferably, the material is a titanium-aluminum composite material; the titanium-aluminum composite material is applied to mobile phone housings or medical devices.

[0028] The cleaning agent for removing laser-carved dust after laser engraving of the titanium-aluminum composite material of the present invention is specially developed for laser-carved dust, has a reasonable pH value through scientific screening and formulation, can completely clean and remove the laser-carved dust around titanium alloy, aluminum alloy and plastic jacks after laser engraving of the titanium-aluminum composite material, has no adverse effect on the surface of the aluminum alloy, and has an excellent cleaning effect on the laser-carved dust; can ensure the cleanliness and brightness of the product; and can effectively improve production efficiency and reduce energy consumption when used at a relatively low operating temperature, that is, when used in an ultrasonic cleaning temperature of 50 to 55°C. DETAILED DESCRIPTION

[0029] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, they are described in detail below in conjunction with specific embodiments.

[0030] The embodiment of the present invention provides a cleaning agent for removing laser-carved dust after laser carving of titanium-aluminum composite materials, and the cleaning agent includes: an acidic agent, a corrosion inhibitor, a solvent and water; the acidic agent is selected from one or more of hydroxyethylidene diphosphonic acid, aminotri (methylene phosphonic acid), ethylenediaminetetra (methylene phosphonic acid), and diethylenetriaminepenta (methylene phosphonic acid); the molecular formula of hydroxyethylidene diphosphonic acid is C2H8O7P2, which is easily soluble in water, soluble in methanol and ethanol, has a large dissociation constant in water, and can form stable complexes with metal ions. It can form stable adducts with compounds containing active oxygen to keep the active oxygen stable. In the present invention, it can be used as the main component of the cleaning agent and can have a good removal effect on laser-carved dust. The molecular formula of aminotri (methylene phosphonic acid) is C3H 12 NO9P3 is miscible with water and can form stable complexes with metal ions. It has good dispersibility and has good corrosion inhibition effect when the concentration in water is high. The molecular formula of EDTA is C6H 20 N2O 12 P4 has strong chelating properties and can form stable complexes with metal ions. The molecular formula of diethylenetriaminepenta(methylenephosphonic acid) is C9H 28 O 15N3P5 has good corrosion inhibition and inhibition effects, can effectively inhibit the corrosion of metal materials, form a tight corrosion inhibition film, prevent further corrosion of metal materials, and is easily soluble in acidic solutions. It has excellent scale inhibition and corrosion inhibition effects and good temperature resistance. Its scale inhibition and corrosion inhibition performance in alkaline environments is better than other organic phosphorus. In the present invention, the acidic agent is selected from at least two of hydroxyethylidene diphosphonic acid, aminotri (methylene phosphonic acid), ethylenediamine tetra (methylene phosphonic acid), and diethylenetriamine penta (methylene phosphonic acid); the synergistic effect of two or more acidic agents can better clean the laser carving ash. More preferably, the acidic agent adopts a composite acidic agent of hydroxyethylidene diphosphonic acid combined with at least one of aminotri (methylene phosphonic acid), ethylenediamine tetra (methylene phosphonic acid), and diethylenetriamine penta (methylene phosphonic acid), which has a better cleaning effect.

[0031] The corrosion inhibitor is selected from one or more of sodium benzotriazole, sodium mercaptobenzothiazole, methylbenzotriazole, and imidazoline corrosion inhibitors; preferably, the corrosion inhibitor is selected from at least two of sodium benzotriazole, sodium mercaptobenzothiazole, methylbenzotriazole, and imidazoline corrosion inhibitors; the synergistic effect of two or more corrosion inhibitors can significantly reduce the reaction between the acidic agent and the aluminum alloy, so that the cleaning agent has no adverse effect on the aluminum alloy. Sodium benzotriazole can be adsorbed on the surface of the metal to form a protective film, and has a good corrosion inhibition effect in the circulating cooling water system; sodium mercaptobenzothiazole, methylbenzotriazole, and imidazoline corrosion inhibitors have good corrosion inhibition effects on metals, including aluminum and copper. More preferably, the corrosion inhibitor is a composite corrosion inhibitor of sodium benzotriazole combined with at least one of sodium mercaptobenzothiazole, toluenetriazole, and imidazoline corrosion inhibitor, which has a better slow-release effect.

[0032] The solvent is selected from one or more of ethanol, glycerol, isopropanol, isohexanediol, diethylene glycol, propylene glycol methyl ether, and dipropylene glycol butyl ether; preferably, the solvent is selected from at least two of ethanol, glycerol, isopropanol, isohexanediol, diethylene glycol, propylene glycol methyl ether, and dipropylene glycol butyl ether; preferably, the water is deionized pure water, and the solvent composition can make the acidic agent and the corrosion inhibitor better dissolved in the solvent and water, so as to obtain a fully dissolved laser ash cleaning agent.

[0033] The inventors of the present invention have found through long-term experiments that an acidic agent using hydroxyethylidene diphosphonic acid in combination with at least one of aminotri (methylene phosphonic acid), ethylenediaminetetra (methylene phosphonic acid), and diethylenetriaminepenta (methylene phosphonic acid) has a better cleaning effect on laser-carved ash in the present system. The principle is that both have acidity and dispersibility, while hydroxyethylidene diphosphonic acid has a better stable complexation property and aminotri (methylene phosphonic acid), ethylenediaminetetra (methylene phosphonic acid), and diethylenetriaminepenta (methylene phosphonic acid) have a better corrosion inhibition property. The composite effect has both the removal effect on laser-carved ash and the corrosion inhibition and protection effect on titanium-aluminum composite materials.

[0034] In the cleaning agent, the weight proportions of each component are: the acidic agent is 10-20 weight proportions, the corrosion inhibitor is 3-10 weight proportions, the solvent is 5-15 weight proportions, and the water is 40-60 weight proportions. The cleaning agent with the above components and contents can have a better cleaning effect on the laser-carved ash when used in an ultrasonic cleaning temperature of 50-55°C. Preferably, in the cleaning agent, the weight proportions of each component are: the pure water is 40-45 weight proportions, the acidic agent is 12-18 weight proportions, the corrosion inhibitor is 4-5 weight proportions, and the solvent is 8-12 weight proportions; the preferred components and contents of the cleaning agent have an excellent cleaning effect on the laser-carved ash. In the cleaning agent, increasing the mass proportion of the acidic agent and correspondingly reducing the mass proportion of pure water can correspondingly improve the cleaning performance of the laser-carved ash; however, if the mass proportion of the acidic agent is too high, it may cause corrosion to the titanium-aluminum composite material.

[0035] In a preferred embodiment of the present invention, the cleaning agent further comprises a surfactant; the surfactant is selected from one or more of alkyl glycosides, alkylphenol polyoxyethylene ethers, octylphenol polyoxyethylene ethers, sodium alkylbenzene sulfonates, isomeric tetradecanol polyoxyethylene ethers, and lauryl alcohol polyoxyethylene ethers; alkyl glycosides can be compounded with various ionic and nonionic surfactants to produce a synergistic effect. Alkylphenol polyoxyethylene ethers are an important polyoxyethylene nonionic surfactant with the characteristics of stable properties, acid and alkali resistance, and low cost. Octylphenol polyoxyethylene ethers have good emulsification, dispersion, and antistatic properties, and can enhance the surface activity of metals when used in combination with alkyl glycosides. Sodium alkylbenzene sulfonate is easy to oxidize, has strong foaming power, high detergency, and is easy to compound with various additives. It is a very excellent anionic surfactant. When used in combination with the above-mentioned surfactants, better comprehensive washing effects can be obtained. Isomeric alcohol polyoxyethylene ethers have strong emulsification ability, high surface activity, resistance to hard water, good chemical stability and environmental compatibility in a wide pH range, and can be used in combination with the above-mentioned other surfactants to obtain better comprehensive washing effects. Lauryl alcohol polyoxyethylene ether has excellent washing, emulsifying, dispersing, wetting, solubilizing and other functions, and has strong foaming power, easy rinsing, and excellent detergency; it is one of the surfactants with the lowest skin irritation; compounding with the above-mentioned other surfactants can reduce their irritation and improve the performance of the product. Preferably, the surfactant is selected from at least two of alkyl glycosides, alkylphenol polyoxyethylene ethers, octylphenol polyoxyethylene ethers, sodium alkylbenzene sulfonates, isomeric tetradecanol polyoxyethylene ethers, and lauryl alcohol polyoxyethylene ethers; in the cleaning agent, the surfactant is 15 to 25 parts by weight. Preferably, the surfactant is 18 to 25 parts by weight. Adding the surfactant can wet the surface of the titanium-aluminum composite material, so that the laser-carved ash is better dispersed in the cleaning agent, and the cleaning agent is enhanced. The surfactant with the preferred content and composition has a better solubilizing effect and significantly improves the cleaning agent's removal of laser-carved ash.

[0036] In a preferred embodiment of the present invention, the cleaning agent further comprises a builder; the builder is selected from one or more of sodium tripolyphosphate, sodium dihydrogen phosphate, potassium sodium tartrate, sodium carbonate, triethanolamine, and sodium sulfate; the builder is selected from at least two of sodium tripolyphosphate, sodium dihydrogen phosphate, potassium sodium tartrate, sodium carbonate, triethanolamine, and sodium sulfate; in the cleaning agent, the builder is 10 to 20 parts by weight, preferably, the builder is 12 to 18 parts by weight. The builder can improve the cleaning effect of the surfactant, enhance the cleaning agent's removal effect on laser-carved ash, and prevent the scaling of laser-carved ash in the cleaning agent.

[0037] In a preferred embodiment of the present invention, a method for preparing a cleaning agent for removing laser engraving ash after laser engraving of a titanium-aluminum composite material is provided, comprising the following steps:

[0038] Step 1: Prepare pure water: Weigh pure water and keep the temperature at 30-40℃.

[0039] Step 2, preparing a mixture containing an acidic agent: adding an acidic agent to pure water, stirring and dissolving completely, to obtain a mixture containing an acidic agent; the acidic agent is selected from one or more of hydroxyethylidene diphosphonic acid, aminotri(methylene)phosphonic acid, ethylenediaminetetra(methylene)phosphonic acid, and diethylenetriaminepenta(methylene)phosphonic acid.

[0040] Step 3, preparing a mixture containing a corrosion inhibitor: adding a corrosion inhibitor to a mixture containing an acidic agent, stirring and dissolving the mixture completely, to obtain a mixture containing an acidic agent and a corrosion inhibitor; the corrosion inhibitor is selected from one or more of sodium benzotriazole, sodium mercaptobenzothiazole, methylbenzotriazole, and imidazoline corrosion inhibitors.

[0041] Step 4, preparing a mixture containing a builder: adding the builder to the mixture containing the acidic agent and the corrosion inhibitor, stirring and dissolving completely, to obtain a mixture containing the acidic agent, the corrosion inhibitor and the builder; the builder is selected from one or more of sodium tripolyphosphate, sodium dihydrogen phosphate, potassium sodium tartrate, sodium carbonate, triethanolamine, and sodium sulfate.

[0042] Step 5, preparing a mixture containing a surfactant: adding a surfactant to a mixture containing an acidic agent, a corrosion inhibitor and a builder, stirring and dissolving the surfactant completely, and obtaining a mixture containing an acidic agent, a corrosion inhibitor, a surfactant and a builder; the surfactant is selected from a combination of one or more of alkyl glycosides, alkylphenol polyoxyethylene ethers, octylphenol polyoxyethylene ethers, sodium alkylbenzene sulfonates, isomeric tetradecanol polyoxyethylene ethers, and lauryl alcohol polyoxyethylene ethers.

[0043] Step 6: Prepare a mixture containing a solvent: add a solvent to the mixture containing an acidic agent, a corrosion inhibitor, a surfactant and a builder, stir and dissolve completely, and obtain a cleaning agent for removing laser engraving ash after laser engraving of a titanium-aluminum composite material; the solvent is selected from one or more of ethanol, glycerol, isopropanol, isohexylene glycol, diethylene glycol, propylene glycol methyl ether, and dipropylene glycol butyl ether.

[0044] In a preferred embodiment of the present invention, a method for cleaning a workpiece by removing laser engraving ash cleaning agent after laser engraving of a titanium-aluminum composite material is provided, comprising the following steps:

[0045] Step 1, add an appropriate amount of pure water to the first ultrasonic cleaning tank, accurately weigh the cleaning agent for removing the laser carving ash after laser carving of the titanium-aluminum composite material, add it to the first ultrasonic cleaning tank, and prepare it into the first cleaning agent;

[0046] Step 2, in a first ultrasonic cleaning tank, the workpiece to be cleaned is first cleaned with a first cleaning agent to obtain a first cleaned workpiece; wherein the workpiece to be cleaned is a titanium-aluminum composite workpiece after laser engraving; in this step, the concentration of the cleaning agent for removing laser engraving ash after laser engraving of the titanium-aluminum composite material in the first cleaning agent is 8% to 10%; the ultrasonic frequency and current of the first cleaning are 40 to 50 khz, 0.8 to 1.2 A, the temperature of the first cleaning is 50 to 55° C., and the cleaning time is 5 to 10 minutes;

[0047] Step 3, add an appropriate amount of pure water to the second ultrasonic cleaning tank, accurately weigh the cleaning agent for removing the laser carving ash after laser carving of the titanium-aluminum composite material, add it to the second ultrasonic cleaning tank, and prepare it into the second cleaning agent;

[0048] Step 4, in a second ultrasonic cleaning tank, the first cleaning workpiece is subjected to a second cleaning with a second cleaning agent to obtain a second cleaning workpiece; in this step, the concentration of the cleaning agent for removing laser carving ash after laser carving of the titanium-aluminum composite material in the second cleaning agent is 8% to 10%, the ultrasonic frequency of the second cleaning is 40 to 50 khz, 0.8 to 1.2A, the temperature of the second cleaning is 50 to 55°C, and the cleaning time is 5 to 10 minutes.

[0049] Step 5: Perform triple water washing on the second cleaned workpiece, and after washing, dry it at 75-80° C. for 20-30 min to obtain the target workpiece.

[0050] In a preferred embodiment of the present invention, an application of a cleaning agent for removing laser engraving dust is provided, and the application includes: an application for preparing a reagent or product for removing laser engraving dust; an application for material cleaning; or an application for workpiece production in combination with a laser engraving machine. Preferably, the material is a titanium-aluminum composite material; the titanium-aluminum composite material is used in mobile phone housings or medical devices.

[0051] The cleaning agent for removing laser-carved dust after laser engraving of the titanium-aluminum composite material in the preferred embodiment of the present invention is specially developed for laser-carved dust. It has a reasonable pH value through scientific screening and formulation, and can completely clean and remove the laser-carved dust around titanium alloy, aluminum alloy and plastic jacks after laser engraving of the titanium-aluminum composite material. At the same time, it has no adverse effect on the surface of the aluminum alloy and has an excellent cleaning effect on the laser-carved dust; it can ensure the cleanliness and brightness of the product; it can be used at a lower operating temperature, that is, when used in an ultrasonic cleaning temperature of 50 to 55°C, it can effectively improve production efficiency and reduce energy consumption.

[0052] The present invention is described in detail below in conjunction with specific embodiments 1 to 12.

[0053] Examples 1 to 12 are tests for the effects of adding different types and amounts of acidic agents, corrosion inhibitors, surfactants and detergents on the removal of laser-engraved dust from titanium-aluminum composite materials after laser engraving.

[0054] Example 1 Cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite material and preparation method thereof

[0055] Example 1 uses a two-component acidic agent, a surfactant, a builder, a solvent, and a single-component corrosion inhibitor;

[0056] Prepare the raw materials for removing laser-engraved dust cleaning agent after laser engraving of titanium-aluminum composite materials, including: 40% pure water; 8% hydroxyethylidene diphosphonic acid, 8% aminotrimethylphosphonic acid; 4% sodium benzotriazole; 4% sodium tripolyphosphate, 10% sodium dihydrogen phosphate; 8% alkyl glycoside, 8% alkylphenol polyoxyethylene ether; 5% ethanol, 5% glycerol.

[0057] Preparation method: ① first add pure water and keep the temperature at 30-40°C; ② add the acidic agent and stir to dissolve completely; ③ slowly add the corrosion inhibitor while stirring and dissolving completely; ④ add the detergent in sequence and stir to dissolve completely; ⑤ add the surfactant in sequence and stir to dissolve completely; ⑥ add the solvent in sequence and continue stirring for 20 minutes after stirring to dissolve completely, to obtain the cleaning agent of Example 1.

[0058] Example 2 Cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite material and preparation method thereof

[0059] Example 2 uses a two-component acidic agent, a surfactant, a builder, a solvent, and a single-component corrosion inhibitor, and the raw materials used for each component are different from those in Example 1;

[0060] The raw materials for preparing a cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials include: 45% pure water; 6% aminotri(methylenephosphonic acid), 6% ethylenediaminetetra(methylenephosphonic acid); 4% sodium mercaptobenzothiazole; 6% sodium dihydrogen phosphate, 6% potassium sodium tartrate; 12% alkylphenol polyoxyethylene ether, 4% octylphenol polyoxyethylene ether; 4% glycerol, 7% isopropyl alcohol.

[0061] Preparation method: ① first add pure water and keep the temperature at 30-40℃; ② add acidic agent and stir to dissolve completely; ③ slowly add corrosion inhibitor while stirring and dissolving completely; ④ add detergent in sequence and stir to dissolve completely; ⑤ add surfactant in sequence and stir to dissolve completely; ⑥ add solvent in sequence and continue stirring for 20 minutes after stirring to dissolve completely, to obtain the cleaning agent of Example 2.

[0062] Example 3 Cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite material and preparation method thereof

[0063] Example 3 uses a two-component acidic agent, a surfactant, a builder, a solvent, and a single-component corrosion inhibitor, and the raw materials used for each component are different from those in Example 1;

[0064] The raw materials for the cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials are prepared, including: 43% pure water; 4% hydroxyethylidene diphosphonic acid, 5% diethylenetriamine penta (methylene phosphonic acid); 4% methylbenzotriazole; 6% potassium sodium tartrate, 12% sodium carbonate; 6% octylphenol polyoxyethylene ether, 12% isomeric tetradecanol polyoxyethylene ether; 4% isohexanediol, 4% diethylene glycol.

[0065] Preparation method: ① first add pure water and keep the temperature at 30-40℃; ② add acidic agent and stir to dissolve completely; ③ slowly add corrosion inhibitor while stirring and dissolving completely; ④ add detergent in sequence and stir to dissolve completely; ⑤ add surfactant in sequence and stir to dissolve completely; ⑥ add solvent in sequence and continue stirring for 20 minutes after stirring to dissolve completely, to obtain the cleaning agent of Example 3.

[0066] Example 4 Cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite material and preparation method thereof

[0067] Example 4 uses a two-component acidic agent, a surfactant, and a builder, and a single-component corrosion inhibitor and solvent, and the raw materials used for each component are different from those in Example 1;

[0068] The raw materials for the cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials are prepared, including: 41% pure water; 6% aminotri(methylenephosphonic acid), 12% diethylenetriaminepenta(methylenephosphonic acid); 5% imidazoline corrosion inhibition; 6% triethanolamine, 6% sodium sulfate; 14% isomeric tetradecanol polyoxyethylene ether, 2% lauryl alcohol polyoxyethylene ether; 8% isohexanediol.

[0069] Preparation method: ① first add pure water and keep the temperature at 30-40℃; ② add acidic agent and stir to dissolve completely; ③ slowly add corrosion inhibitor while stirring and dissolving completely; ④ add detergent in sequence and stir to dissolve completely; ⑤ add surfactant in sequence and stir to dissolve completely; ⑥ add solvent in sequence and continue stirring for 20 minutes after stirring to dissolve completely, to obtain the cleaning agent of Example 4.

[0070] Example 5 Cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite material and preparation method thereof

[0071] Example 5 uses a two-component acidic agent and a builder, a three-component surfactant, and a single-component corrosion inhibitor and solvent. The raw materials used for each component are different from those in Example 1.

[0072] The raw materials for preparing a cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials include: 43% pure water; 3% aminotri(methylenephosphonic acid), 9% diethylenetriaminepenta(methylenephosphonic acid); 4% methylbenzotriazole; 6% sodium dihydrogen phosphate, 6% triethanolamine; 6% alkyl glycoside, 6% sodium alkylbenzene sulfonate, 8% isomeric tetradecanol polyoxyethylene ether; 4% diethylene glycol, 5% propylene glycol methyl ether.

[0073] Preparation method: ① first add pure water and keep the temperature at 30-40℃; ② add acidic agent and stir to dissolve completely; ③ slowly add corrosion inhibitor while stirring and dissolving completely; ④ add detergent in sequence and stir to dissolve completely; ⑤ add surfactant in sequence and stir to dissolve completely; ⑥ add solvent in sequence and continue stirring for 20 minutes after stirring to dissolve completely to obtain the cleaning agent of Example 5.

[0074] Example 6 Cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite material and preparation method thereof

[0075] Example 6 uses a two-component acidic agent, a builder, a surfactant, a corrosion inhibitor and a single-component solvent, and the raw materials used for each component are different from those in Example 1;

[0076] The raw materials for the cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials are prepared, including: 48% pure water; 6% aminotri(methylenephosphonic acid), 12% diethylenetriaminepenta(methylenephosphonic acid); 2% methylbenzotriazole, 2% imidazoline corrosion inhibitor; 6% sodium carbonate, 6% triethanolamine; 6% alkylphenol polyoxyethylene ether, 6% octylphenol polyoxyethylene ether; 6% isopropyl alcohol.

[0077] Preparation method: ① first add pure water and keep the temperature at 30-40℃; ② add acidic agent and stir to dissolve completely; ③ slowly add corrosion inhibitor while stirring and dissolving completely; ④ add detergent in sequence and stir to dissolve completely; ⑤ add surfactant in sequence and stir to dissolve completely; ⑥ add solvent in sequence and continue stirring for 20 minutes after stirring to dissolve completely to obtain the cleaning agent of Example 6.

[0078] Example 7 Cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite material and preparation method thereof

[0079] Example 7 uses a two-component acidic agent, a surfactant, a builder, a solvent, and a corrosion inhibitor. The difference from Example 1 is that a two-component corrosion inhibitor is used;

[0080] The raw materials for preparing a cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials include: 40% pure water; 8% hydroxyethylidene diphosphonic acid, 8% aminotri(methylene)phosphonic acid; 2% sodium benzotriazole, 2% sodium mercaptobenzothiazole; 4% sodium tripolyphosphate, 10% sodium dihydrogen phosphate; 8% alkyl glycoside, 8% alkylphenol polyoxyethylene ether; 5% ethanol, 5% glycerol.

[0081] Preparation method: ① first add pure water and keep the temperature at 30-40℃; ② add acidic agent and stir to dissolve completely; ③ slowly add corrosion inhibitor while stirring and dissolving completely; ④ add detergent in sequence and stir to dissolve completely; ⑤ add surfactant in sequence and stir to dissolve completely; ⑥ add solvent in sequence and continue stirring for 20 minutes after stirring to dissolve completely to obtain the cleaning agent of Example 7.

[0082] Example 8 Cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite material and preparation method thereof

[0083] Example 8 uses a two-component acidic agent, solvent, and corrosion inhibitor, and the difference from Example 7 is that no builder and surfactant are added;

[0084] The raw materials for the cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials are prepared, including: 60% pure water; 10% hydroxyethylidene diphosphonic acid, 10% aminotrimethylphosphonic acid; 5% sodium benzotriazole, 5% sodium mercaptobenzothiazole; 5% ethanol, and 5% propylene glycol.

[0085] Preparation method: ① first add pure water and keep the temperature at 30-40°C; ② add acidic agent and stir to dissolve completely; ③ slowly add corrosion inhibitor while stirring to dissolve completely; ④ add solvents in sequence, continue stirring for 20 minutes after stirring to dissolve completely, to obtain the cleaning agent of Example 8.

[0086] Example 9 Cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite material and preparation method thereof

[0087] Example 9 uses a two-component acidic agent, solvent, corrosion inhibitor, and surfactant, and the difference from Example 7 is that no builder is added;

[0088] The raw materials for the cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials are prepared, including: 50% pure water; 10% hydroxyethylidene diphosphonic acid, 10% aminotri(methylene)phosphonic acid; 2% sodium benzotriazole, 2% sodium mercaptobenzothiazole; 8% alkyl glycoside, 8% alkylphenol polyoxyethylene ether; 5% ethanol, 5% propylene glycol.

[0089] Preparation method: ① first add pure water and keep the temperature at 30-40℃; ② add acidic agent and stir to dissolve completely; ③ slowly add corrosion inhibitor while stirring and dissolving completely; ④ add detergent in sequence and stir to dissolve completely; ⑤ add surfactant in sequence and stir to dissolve completely; ⑥ add solvent in sequence and continue stirring for 20 minutes after stirring to dissolve completely to obtain the cleaning agent of Example 9.

[0090] Example 10 Cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite material and preparation method thereof

[0091] Example 10 uses a two-component acidic agent, solvent, corrosion inhibitor, surfactant and builder, and the difference from Example 5 is that a two-component corrosion inhibitor is added;

[0092] The raw materials for preparing a cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials include: 43% pure water; 3% aminotri(methylenephosphonic acid), 9% diethylenetriaminepenta(methylenephosphonic acid); 2% sodium benzotriazole, 2% methylbenzotriazole; 6% sodium dihydrogen phosphate, 6% triethanolamine; 6% alkyl glycoside, 6% sodium alkylbenzene sulfonate, 8% polyoxyethylene isomerate tetradecanol; 4% diethylene glycol, 5% propylene glycol methyl ether.

[0093] Preparation method: ① first add pure water and keep the temperature at 30-40℃; ② add acidic agent and stir to dissolve completely; ③ slowly add corrosion inhibitor while stirring and dissolving completely; ④ add detergent in sequence and stir to dissolve completely; ⑤ add surfactant in sequence and stir to dissolve completely; ⑥ add solvent in sequence and continue stirring for 20 minutes after stirring to dissolve completely to obtain the cleaning agent of Example 10.

[0094] Example 11 Cleaning agent for removing laser engraving dust after laser engraving of titanium-aluminum composite materials and preparation method thereof

[0095] Example 11 uses a two-component acidic agent, solvent, corrosion inhibitor, surfactant and builder, and the difference from Example 6 is that a two-component solvent is added;

[0096] The raw materials for the cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials are prepared, including: 40% pure water; 8% hydroxyethylidene diphosphonic acid, 8% aminotri(methylene)phosphonic acid; 4% sodium benzotriazole, 4% sodium tripolyphosphate, 10% sodium dihydrogen phosphate; 8% alkyl glycoside, 8% alkylphenol polyoxyethylene ether; 5% ethanol, 5% propylene glycol.

[0097] Preparation method: ① first add pure water and keep the temperature at 30-40℃; ② add acidic agent and stir to dissolve completely; ③ slowly add corrosion inhibitor while stirring and dissolving completely; ④ add detergent in sequence and stir to dissolve completely; ⑤ add surfactant in sequence and stir to dissolve completely; ⑥ add solvent in sequence and continue stirring for 20 minutes after stirring to dissolve completely to obtain the cleaning agent of Example 11.

[0098] Example 12 Cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite material and preparation method thereof

[0099] The difference from Example 1 is that a single-component acidic agent is used;

[0100] Prepare the raw materials for removing laser engraving dust from titanium-aluminum composite materials after laser engraving, including: 40% pure water; 16% hydroxyethylidene diphosphonic acid; 4% sodium benzotriazole; 4% sodium tripolyphosphate, 10% sodium dihydrogen phosphate; 8% alkyl glycoside, 8% alkylphenol polyoxyethylene ether; 5% ethanol, 5% glycerol

[0101] Preparation method: ① first add pure water and keep the temperature at 30-40°C; ② add the acidic agent and stir to dissolve completely; ③ slowly add the corrosion inhibitor while stirring and dissolving completely; ④ add the detergent in sequence and stir to dissolve completely; ⑤ add the surfactant in sequence and stir to dissolve completely; ⑥ add the solvent in sequence and continue stirring for 20 minutes after stirring to dissolve completely, to obtain the cleaning agent of Example 1.

[0102] Test verification

[0103] The cleaning agent of Example 1-12 was used for the cleaning process test. The volume of the cleaning tank reagent was 250L. The detailed process is shown in Table 1 below. The cleaning life was 48 hours, and the number of good products was continuously cleaned. The requirements for good products were that the aluminum alloy was clean and bright without any corrosion, and there was no laser engraving dust around the titanium alloy, aluminum alloy, and plastic jack in the laser engraving area, and there was no shadow of laser engraving dust. There was no laser engraving dust under a 500x magnifying glass.

[0104] Table 1: Specific process of experimental formula 1

[0105]

[0106] The comparative example is based on the HH-408 cleaning agent actually used by customers in this field. The comparative example 1 is based on the process standard originally produced by the customer. The detailed process is shown in the table below:

[0107] Table 2: Specific process of customer HH-408 cleaning agent

[0108]

[0109] Based on the actual application data of customers, the products were put into production for 48 hours continuously, and the yield rate was calculated after full inspection. The inspection standard is that the aluminum alloy has no whitish color, the color near the laser engraving area is uniform, there is no laser engraving gray shadow, and there is no laser engraving gray-black particles under a 500x magnifying glass.

[0110] Table 3: Yield comparison table of Examples 1-12 and Comparative Example 1

[0111]

[0112]

[0113] Test conclusion: The following conclusions can be drawn from the above verification:

[0114] 1. From the comparative tests of Examples 1-12 and the comparative examples, it can be seen that:

[0115] (1) The yield of the laser ash cleaning agent of Examples 1-12 is greater than or equal to 99.0% after continuous verification for 48 hours, which can meet the normal production requirements of customers;

[0116] (2) The normal operating temperature of the laser ash cleaning agent of Example 1-12 is 50-55°C, which is at least 20°C lower than the operating temperature of 75°C of the HH-408 cleaning agent actually used by customers. It is more energy-saving and environmentally friendly;

[0117] (3) The product yield of the laser ash cleaning agents of Examples 1-12, even the laser ash cleaning machine with the most basic components, is higher than that of the HH-408 cleaning agent previously used by customers in the field of comparative example 1.

[0118] Second, from the comparative data of Examples 1-12, it can be seen that:

[0119] (1) Increasing the weight fraction of the acidic agent and correspondingly reducing the weight fraction of pure water can improve the cleaning performance of the laser-carved ash accordingly; however, if the weight fraction of the acidic agent is too high, it may cause corrosion to the titanium-aluminum composite material. The best effect is achieved when the weight fraction of pure water is 40 to 45 parts by weight and the weight fraction of the acidic agent is 12 to 18 parts by weight.

[0120] (2) The synergistic effect of two or more acidic agents, corrosion inhibitors, builders, surfactants and solvents can achieve a better cleaning effect of laser-engraved ash than using a single component.

[0121] (3) The use of surfactants and / or builders has a better cleaning effect than cleaning agents without surfactants and builders.

[0122] (4) A composite acidic agent of hydroxyethylidene diphosphonic acid combined with at least one of aminotri (methylene phosphonic acid), ethylenediaminetetra (methylene phosphonic acid), and diethylenetriaminepenta (methylene phosphonic acid) has a better cleaning effect.

[0123] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials, characterized in that: The cleaning agent comprises: an acidic agent, a corrosion inhibitor, a solvent and water; The acidic agent is a composite acidic agent of hydroxyethylidene diphosphonic acid combined with at least one of aminotrimethylenephosphonic acid, ethylenediaminetetramethylenephosphonic acid, and diethylenetriaminepentamethylenephosphonic acid; The corrosion inhibitor is a composite corrosion inhibitor of sodium benzotriazole combined with sodium mercaptobenzothiazole, toluenetriazole and imidazoline corrosion inhibitor; The solvent is selected from at least two of ethanol, glycerol, isopropanol, isohexylene glycol, diethylene glycol, propylene glycol methyl ether, and dipropylene glycol butyl ether; In the cleaning agent, the weight proportions of the components are: the acidic agent is 10 to 20 weight proportions, the corrosion inhibitor is 3 to 10 weight proportions, the solvent is 5 to 15 weight proportions, and the water is 40 to 60 weight proportions.

2. The cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials according to claim 1, characterized in that: The water is deionized pure water; In the cleaning agent, the weight proportions of the components are: the pure water is 40 to 45 parts by weight, the acidic agent is 12 to 18 parts by weight, the corrosion inhibitor is 4 to 5 parts by weight, and the solvent is 8 to 12 parts by weight.

3. The cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials according to claim 1, characterized in that: The cleaning agent also includes a surfactant and a builder; The surfactant is selected from one or more of alkyl glycosides, alkylphenol polyoxyethylene ethers, octylphenol polyoxyethylene ethers, sodium alkylbenzene sulfonates, isomeric tetradecanol polyoxyethylene ethers, and lauryl alcohol polyoxyethylene ethers; The builder is selected from one or more of sodium tripolyphosphate, sodium dihydrogen phosphate, potassium sodium tartrate, sodium carbonate, triethanolamine, and sodium sulfate; In the cleaning agent, the builder is 10 to 20 parts by weight, and the surfactant is 15 to 25 parts by weight.

4. The cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials according to claim 3 is characterized in that: The surfactant is selected from at least two of alkyl glycosides, alkylphenol polyoxyethylene ethers, octylphenol polyoxyethylene ethers, sodium alkylbenzene sulfonates, isomeric tetradecanol polyoxyethylene ethers, and lauryl alcohol polyoxyethylene ethers; The builder is selected from at least two of sodium tripolyphosphate, sodium dihydrogen phosphate, potassium sodium tartrate, sodium carbonate, triethanolamine, and sodium sulfate; In the cleaning agent, the builder is 12 to 18 parts by weight, and the surfactant is 18 to 25 parts by weight.

5. A method for preparing a cleaning agent for removing laser engraving dust after laser engraving of a titanium-aluminum composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Steps for preparing pure water: weigh pure water and keep the temperature at 30-40℃; The steps of preparing a mixture containing an acidic agent include: adding an acidic agent to pure water, stirring and dissolving the acidic agent completely, and obtaining a mixture containing an acidic agent; the acidic agent is a composite acidic agent of hydroxyethylidene diphosphonic acid combined with at least one of aminotri(methylene)phosphonic acid, ethylenediaminetetra(methylene)phosphonic acid, and diethylenetriaminepenta(methylene)phosphonic acid; The step of preparing a mixture containing a corrosion inhibitor is as follows: adding the corrosion inhibitor to the mixture containing an acidic agent, stirring and dissolving the mixture completely, and obtaining a mixture containing the acidic agent and the corrosion inhibitor; the corrosion inhibitor is a composite corrosion inhibitor of sodium benzotriazole combined with sodium mercaptobenzothiazole, toluene triazole, and imidazoline corrosion inhibitor; The step of preparing a mixture containing a solvent is as follows: adding a solvent to a mixture containing an acidic agent and a corrosion inhibitor, stirring and dissolving the solvent completely, and obtaining a cleaning agent for removing laser engraving ash after laser engraving of a titanium-aluminum composite material; the solvent is selected from at least two of ethanol, glycerol, isopropanol, isohexanediol, diethylene glycol, propylene glycol methyl ether, and dipropylene glycol butyl ether.

6. The preparation method according to claim 5, characterized in that: Between the step of preparing a mixture containing a corrosion inhibitor and the step of preparing a mixture containing a solvent, the following steps are also included: The step of preparing a mixture containing a builder is as follows: adding the builder to a mixture containing an acidic agent and a corrosion inhibitor, stirring and dissolving the mixture completely, and obtaining a mixture containing an acidic agent, a corrosion inhibitor and a builder; the builder is selected from one or more of sodium tripolyphosphate, sodium dihydrogen phosphate, potassium sodium tartrate, sodium carbonate, triethanolamine, and sodium sulfate; The steps of preparing a mixture containing a surfactant are as follows: adding a surfactant to a mixture containing an acidic agent, a corrosion inhibitor and a builder, stirring and dissolving the mixture completely, and obtaining a mixture containing an acidic agent, a corrosion inhibitor, a surfactant and a builder; then adding the solvent to the mixture, stirring and dissolving the mixture completely, and obtaining a cleaning agent for removing laser-engraved ash after laser engraving of a titanium-aluminum composite material; the surfactant is selected from a combination of one or more of alkyl glucoside, alkylphenol polyoxyethylene ether, octylphenol polyoxyethylene ether, sodium alkylbenzene sulfonate, isomeric tetradecanol polyoxyethylene ether, and lauryl alcohol polyoxyethylene ether.

7. A method for cleaning a workpiece using the cleaning agent for removing laser engraving ash after laser engraving of a titanium-aluminum composite material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Add an appropriate amount of pure water to the first ultrasonic cleaning tank, accurately weigh the cleaning agent for removing the laser carving ash after laser carving of the titanium-aluminum composite material, add it to the first ultrasonic cleaning tank, and prepare it into the first cleaning agent; In a first ultrasonic cleaning tank, the workpiece to be cleaned is first cleaned with a first cleaning agent to obtain a first cleaned workpiece; wherein the workpiece to be cleaned is a titanium-aluminum composite material workpiece after laser engraving; Add an appropriate amount of pure water to the second ultrasonic cleaning tank, accurately weigh the cleaning agent after laser engraving of the titanium-aluminum composite material to remove the laser engraving ash, add it to the second ultrasonic cleaning tank, and prepare it into the second cleaning agent; Performing a second cleaning on the first cleaning workpiece in a second ultrasonic cleaning tank using a second cleaning agent to obtain a second cleaning workpiece; The second cleaned workpiece is subjected to a triple water washing treatment, and after water washing, is dried at a temperature of 75 to 80° C. for 20 to 30 minutes to obtain a target workpiece.

8. The cleaning method according to claim 7, characterized in that: The concentration of the cleaning agent for removing laser engraving ash after laser engraving of titanium-aluminum composite materials in the first cleaning agent is 8% to 10%; The ultrasonic frequency and current of the first cleaning are 40-50 khz, 0.8-1.2 A, the temperature of the first cleaning is 50-55° C., and the cleaning time is 5-10 min; The concentration of the second cleaning agent for removing laser engraving dust from titanium-aluminum composite materials after laser engraving is 8% to 10%; The ultrasonic frequency of the second cleaning is 40-50 khz, 0.8-1.2A, the temperature of the second cleaning is 50-55°C, and the cleaning time is 5-10 minutes.

9. An application of the cleaning agent for removing laser-engraved dust as claimed in any one of claims 1 to 4, comprising: Application of reagents or products for preparing the removal of laser engraving dust; Applications for material cleaning; Or it can be used in conjunction with a laser engraving machine to produce workpieces.

10. The use of the cleaning agent for removing laser engraving dust according to claim 9, characterized in that: The material is a titanium-aluminum composite material; the titanium-aluminum composite material is used in mobile phone casings or medical devices.

Citation Information

Patent Citations

  • Ultrasonic cleaning agent for aluminium alloy mobile phone shells and preparation method of ultrasonic cleaning agent

    CN105063636A

  • Corrosion inhibitor composition, applications thereof, and method using same to carry out pickling on equipment

    CN105088251A

  • Aluminum alloy cleanser, production method of same, and cleaning method of aluminum alloy

    CN106894029A

  • Cleaning agent for clearing laser carving residue from plastic shell of intelligent mobile terminal and cleaning method

    CN107400566A

  • Cleaning method for residues obtained after laser engraving of mobile phone plastic shell

    CN108587800A